Analisis Kebijakan Dampak Penyesuaian Harga BBM Bersubsidi untuk Nelayan - Iluh Yuliarti; Restiana Panggabean; Habibah Lailatul Farida; Arifin Sutomo Gulo (Studi Akuntansi, Keuangan, dan Manajemen, 2023)
Purpose: The purpose of this research was conducted in order to be able to immediately respond to the policy impact of the increase in fuel prices and to compare fuel prices before and after the stipulation of a fuel price increase. Methodology: The research method used in this research is qualitative research. The data used in this study are primary and secondary data. Secondary data was obtained according to respondents/research samples which were purposively influenced (purposive sampling) including: fishermen in various types of vessels of various sizes. Secondary data was obtained according to research reports, study reports, and data from various related agencies. The data is tabulated and then analyzed narratively and then presented in the form of tables. Results: The results of the study explained that the adjustment of fuel prices had a very large influence on operational costs and business profits. Across all ship sizes, an increase in fuel prices will increase the cost of operating a business or reduce the profitability of a business. Changes in fuel prices, especially diesel fuel, have positive or negative effects on business people, especially fishermen, a decrease in fuel prices has the potential to increase the level of profit received or vice versa, an increase in fuel has the potential to reduce business profit levels. Limitation: The drawbacks of this research are the limited time in searching for primary data in this study, and also the limitations of the place in conducting this research, the place for conducting this research is only done in one place. Contribution: The results obtained through this research can be used as a government consideration in making decisions and can also be used as a reference for future research.